The economic impact of using single-operator cholangioscopy for the treatment of difficult bile duct stones and diagnosis of indeterminate bile duct strictures - Deprez, Pierre H.; Garces Duran, Rodrigo; Moreels, Tom; Furneri, Gianluca; Demma, Federica; Verbeke, Len; Van der Merwe, Schalk W.; Laleman, Wim (Endoscopy, 2018)
Background and study aim Conventional endoscopic retrograde cholangiopancreatography (ERCP) combines endoscopy and radiography to diagnose and treat pathological conditions of the bile duct. The aim of the present analysis was to evaluate the clinical and economic impact of the use of single-operator intraductal cholangioscopy (IDC), which allows for direct visualization of the bile duct, as an alternative to ERCP for the treatment of difficult bile duct stones and the diagnosis of bile duct strictures.Patients and methods The clinical and economic consequences of single-operator IDC use were evaluated using two decision-tree models, one for management of difficult-to-remove stones and one for stricture diagnosis. A hospital perspective was adopted. Data to populate the models were derived from two Belgian hospitals that specialize in endoscopic procedures of the bile duct. Overall, the examined population consisted of 62 patients with difficult stones and 49 patients with indeterminate strictures.Results In the model for difficult stone management, the use of IDC determined a decrease in the number of procedures (– 27 % relative reduction) and costs (– €73 000; – 11 % relative reduction) when compared with ERCP. In the model for stricture diagnosis, the use of IDC determined a decrease in the number of procedures (– 31 % relative reduction) and costs (– €13 000; – 5 % relative variation) when compared with ERCP.Conclusions The single-operator IDC system performed better than ERCP for the treatment of difficult bile duct stones and the diagnosis of bile duct strictures, and reduced the overall expenditure in hospitals in Belgium.